One of Two hemN Genes in Bradyrhizobium japonicum Is Functional during Anaerobic Growth and in Symbiosis - Fischer, Hans-Martin (American Society for Microbiology, 2001)
Previously, we screened the symbiotic gene region of the Bradyrhizobium japonicum chromosome for new NifA-dependent genes by competitive DNA-RNA hybridization (A. Nienaber, A. Huber, M. Göttfert, H. Hennecke, and H. M. Fischer, J. Bacteriol. 182:1472–1480, 2000). Here we report more details on one of the genes identified, a hemN-like gene (now called hemN(1)) whose product exhibits significant similarity to oxygen-independent coproporphyrinogen III dehydrogenases involved in heme biosynthesis in facultatively anaerobic bacteria. In the course of these studies, we discovered that B. japonicum possesses a second hemN-like gene (hemN(2)), which was then cloned by using hemN(1) as a probe. The hemN(2) gene maps outside of the symbiotic gene region; it is located 1.5 kb upstream of nirK, the gene for a Cu-containing nitrite reductase. The two deduced HemN proteins are similar in size (445 and 450 amino acids for HemN(1) and HemN(2), respectively) and share 53% identical (68% similar) amino acids. Expression of both hemN genes was monitored with the help of chromosomally integrated translational lacZ fusions. No significant expression of either gene was detected in aerobically grown cells, whereas both genes were strongly induced (≥20-fold) under microaerobic or anaerobic conditions. Induction was in both cases dependent on the transcriptional activator protein FixK(2). In addition, maximal anaerobic hemN(1) expression was partially dependent on NifA, which explains why this gene had been identified by the competitive DNA-RNA hybridization approach. Strains were constructed carrying null mutations either in individual hemN genes or simultaneously in both genes. All mutants showed normal growth in rich medium under aerobic conditions. Unlike the hemN(1) mutant, strains lacking a functional hemN(2) gene were unable to grow anaerobically under nitrate-respiring conditions and largely failed to fix nitrogen in symbiosis with the soybean host plant. Moreover, these mutants lacked several c-type cytochromes which are normally detectable by heme staining of proteins from anaerobically grown wild-type cells. Taken together, our results revealed that B. japonicum hemN(2), but not hemN(1), encodes a protein that is functional under the conditions tested, and this conclusion was further corroborated by the successful complementation of a Salmonella enterica serovar Typhimurium hemF hemN mutant with hemN(2) only.